Head and Neck MRI Findings in CHARGE Syndrome - Hoch, M.J.; Patel, S.H.; Jethanamest, D.; Win, W.; Fatterpekar, G.M.; Roland, J.T.; Hagiwara, M. (American Journal of Neuroradiology, 2017)
SUMMARY: Coloboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary abnormalities, and Ear abnormalities and deafness (CHARGE) syndrome is a disorder with multiple congenital anomalies seen on imaging. A retrospective review of 10 patients with CHARGE syndrome who underwent MR imaging of the brain as part of a preoperative evaluation for cochlear implantation was conducted. Structural abnormalities of the entire MR imaging of the head were evaluated, including the auditory system, olfactory system, face, skull base, and central nervous system. The most frequent MR imaging findings included dysplasias of the semicircular canals and hypoplasia of the frontal lobe olfactory sulci. Less frequent findings included cleft lip/palate and coloboma. Our study uncovered new findings of a J-shaped sella, dorsal angulation of the clivus, and absent/atrophic parotid glands, not previously described in patients with CHARGE. Our results emphasize the utility of MR imaging in the diagnosis and management of patients with CHARGE syndrome.CHARGEColoboma of the eye, Heart defects, Atresia of the choanae, Retardation of growth and/or development, Genital and/or urinary abnormalities, and Ear abnormalities and deafnessIACinternal auditory canalSCCsemicircular canalSPACEsampling perfection with application-optimized contrasts using different flip angle evolutions